Towards a Simpler Semantics for Systems Biology - Costa Neto, Luis H.; Lifschitz, Sergio; Catanho, Marcos; Miranda, Antônio B. de; Haeusler, Edward H. (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2024)
Computational semantics for molecular biology was introduced to assign activities to biomolecules based on their interactions with environments and other biomolecules. We distinguish between activity and biological function towards an epistemologically neutral semantics that aligns with computational processes. Object Petri Nets (OPNs) represent complex biomolecular activities as compositions of interactions at the nucleotide level. This article introduces a way to transform the networks that shows the equivalence between OPNs and simple Place/Transition (P/T) nets while preserving their semantics. It gives an intuitive understanding of this equivalence and shows OPNs implemented on P/T PNs.